ANALISIS STRUKTUR GEOLOGI BERDASARKAN DATA PERMUKAAN DAERAH BANJARHARJO, KABUPATEN BREBES, PROVINSI JAWA TENGAH: GEOLOGICAL STRUCTURE ANALYSIS BASED ON SURFACE DATA OF THE BANJARHARJO REGION, BREBES DISTRICT, CENTRAL JAVA PROVINCE - Maulana, Ilham; Triany, Novi (Journal of Geoscience Engineering and Energy, 2024)
The research area is administratively located in Banjarharjo Village, Banjarharjo District, Brebes Regency, Central Java Province. Geographically, the research area is located at coordinates 108o 49 '15.4 "- 108o 52' 30.8" East Longitude and 06o 59 "21.8" - 07o 02 '04.8 "LS. The research area is included in The North Central Java Basin (The North Serayu Through/Basin) which is a Back Arc Basin. Based on the stratigraphic and sedimentological composition, the research area is classified into five geological units, (old to young), namely: (1) Sandstone and Claystone Interchange Unit, (2) Carbonate Claystone Unit, (3) Sand Limestone Unit, (4) Volcanic Breccia Unit and (5) Andesite Intrusion Unit. According to Pulonggono and Martodjojo (1994) Java Island, there are three straight lines of dominant structure, including: (1) East Laur - Southwest (Meratus Pattern), (2) North - South (Sundanese Pattern) and (3) West - East (Pattern Java). Based on the strike dip and stockiness data at the research location, the results of the force with the direction of the main stress are relatively Northeast-Southwestern, with the combination of Harding modeling, (1977) and Moody and Hill, (1956). The structural arrangements in the research area that are formed are (1) Cibuluh thrust fault, (2) Maibah sinistral strike-slip fault, (3) Cikuya sinistral strike-slip fault, and (4) Cikuya dextral strikeslip fault.